EFFECT OF SURFACTANTS ON ASCORBIC ACID AND NICOTINIC ACID ATMOSPHERIC OXIDATION KINETICS (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The kinetics of atmospheric oxidation of ascorbic acid and nicotinic acid in aqueous solutions of surfactants has been studied. It has been shown that the kinetics of vitamins’ oxidation process was described by first-order reaction equation. The conditions in which oxidation occurs have great importance: in the pre-micellar region the rate of vitamins’ oxidation increases, while in the postmicellar region it decreases.
Keywords: ascorbic acid, nicotinic acid, surfactant, atmospheric oxidation